JavaScript Design Patterns Deliver Fast and Efficient Production-Grade JavaScript Applications at Scale - Di Francesco, Hugo (Packt Publishing, Limited, 2024)
Chapter 3: Leveraging Behavioral Design Patterns -- Technical requirements -- What are behavioral design patterns? -- The observer pattern in JavaScript -- Implementation -- Use cases of the observer pattern -- Limitations and improvements -- State and strategy in JavaScript and a simplified approach -- Implementation -- Use cases of the state and strategy patterns -- Limitations and improvements -- Visitor in JavaScript -- Implementation -- Use cases of the visitor pattern -- Summary -- Part 2: Architecture and UI Patterns -- Chapter 4: Exploring Reactive View Library Patterns
Description based upon print version of record. - Composing applications with Next.js "zones"
Keywords: JavaScript (Computer program language); Software patterns; Computer software -- Reusability; Scripting languages (Computer science); JavaScript (Langage de programmation); Logiciels; Modèles de conception; Logiciels; Réutilisation; Langages de script (Informatique)